Kesulitan dan Permasalahan dalam Pengajaran Fonetik Bahasa Arab - Ummah, Risa Rifdatul (Maliki Interdisciplinary Journal, 2026)
The teaching of Arabic phonetics is a crucial component in language acquisition, as it determines learners’ accuracy in pronunciation, meaning comprehension, and phonemic discrimination. However, phonetic instruction often encounters various challenges arising from linguistic, psychological, biological, and social factors. Differences between the learners’ native phonological system and Arabic frequently lead to articulation errors, especially with distinctive sounds such as guttural consonants and emphatic phonemes that are seldom found in other languages. Psychological elements—including anxiety, low confidence, and inaccurate sound perception—also influence learners’ ability to produce sounds correctly. Physical limitations, such as hearing impairments, structural abnormalities of the speech organs, or conditions experienced by children after cleft lip surgery, further contribute to phonetic difficulties. The effectiveness of phonetic instruction depends on teachers’ ability to recognize these sources of difficulty and employ appropriate pedagogical strategies. This study aims to identify the primary factors underlying phonetic problems in Arabic language learning and propose more effective instructional approaches to enhance learners’ pronunciation skills. The findings highlight the importance of adopting adaptive, holistic, and learner-sensitive methods to support students with diverse linguistic and physical needs.